Soluble Biobased Substances in soil or Salicylic Acid on leaves affect the foliar pH and soil biovariability of Grapes-as explained by the NIR Spectroscopy of Litterbags and Teabags - Masoero, Giorgio; Sarasso, Giuseppe; Delmastro, Marco; Delmastro, Renato; Antonini, Massimiliano; Solaro, Simone; Scapin, Ivano; Cugnetto, Alberto (Journal of Agronomy Research, 2023)
The purpose of the trial was to check the effects of two grapevine treatments on the plant activity and on the bioactivity and biovariability of the soil. An alkaline complex of Soluble Biobased Substances (SBS) was used in soil at 30 g per plant in a single solution. Salicylic Acid (SA) was used on leaves at 150 mg l-1 every two weeks at 50 ml plant. The plants were examined for their foliar pH and NIR spectra. The soil bioactivity was monitored by means of hay-Litterbag-NIRS (LBN) in combination with the Teabag Index (TBI), using rooibos and green tea that had been buried for 60 days. The evolution of the TBI presented here concerns the TBI-NIRS spectroscopic method used for discriminant analysis. A new algorithm was used to estimate the soil microbiome from the green Teabag spectra. The obtained results showed that the plants and the soil responded to the treatments. In fact, SBS, but not SA, lowered the leaf pH by 5%, an unexpected and original result. Both treatments increased the variability of the leaf composition, with a lower discrimination, based on the NIR spectra, from the Control (75%) to 44% (SA) and 38% (SBS). The TBI method, which is based on weights, was less efficient (67%) than the TBI-NIRS of rooibos (96%) or the LBN of hay (80%), but it was like the TBI-NIRS of green tea (74%). The LBN analyses indicated that the mycorrhizal index had increased by 8% in SA but had reduced by 7% in SBS, while both treatments reduced the activity of the microbes, which did not affect the soil respiration rate. The mineral N in the soil was substantially raised by about 11÷69%. The Taxa profiles showed marked deviations from the Control. Moreover, the SBS treatment reduced the Glomeromycota by 35%, which matched to the reduction in the mycorrhizal index. The most favored Bacteria from the treatments were Proteobateriaand Actinobacteria, with Mortierellomycota being the most penalized. Neither treatment affected the production, but both delayed the technological maturity by 9-11%, while the SBS retarded the phenolic maturity by about 18%. It has been concluded that a simple treatment of vines can affect the bioactivity in the leaves and berries as well as the biovariability of the soil.
Keywords: Soluble Biobased Substances; Salicylic Acid; Foliar pH; Litterbags; Teabags